(untitled) (International Seven Journal of Health Research, 2023)
Introduction: The study of activities of daily living (ADL) in patients with stroke sequelae is of great relevance due to the impact that these sequelae have on the functional independence and quality of life of these individuals. Objective: To examine recent studies on activities of daily living in patients with stroke sequelae in order to understand the difficulties they face and to identify therapeutic interventions and rehabilitation strategies that can improve their conditions. Methodology: This is a literature review article which consisted of a systematic search of the literature in the electronic databases PubMed and Scopus. Key terms related to stroke, daily activities, rehabilitation and quality of life were used. Results: This review showed that the activities of daily living most affected in patients with stroke sequelae are personal independence, mobility and communication. These patients face significant challenges in walking, lifting objects and performing basic self-care tasks, which compromises their autonomy and quality of life. Conclusion: It was observed how important it is to understand the difficulties faced by patients with stroke sequelae in their daily activities, which require the need for appropriate therapeutic interventions and a patient-centered approach in which health professionals and caregivers work together.